Hidden in plain sight: reassessment of the pig-footed bandicoot, Chaeropus ecaudatus (Peramelemorphia, Chaeropodidae), with a description of a new species from central australia, and use of the fossil record to trace its past distribution - Travouillon, Kenny J.; Simões, Bruno F.; Miguez, Roberto Portela; Brace, Selina; Brewer, Philippa; Stemmer, David; Price, Gilbert J.; Cramb, Jonathan; Louys, Julien (Zootaxa, 2019)
The Pig-footed Bandicoot, Chaeropus ecaudatus, an extinct arid-adapted bandicoot, was named in 1838 based on a specimen without a tail from the Murray River in New South Wales. Two additional species were later named, C. castanotis and C. occidentalis, which have since been synonymised with C. ecaudatus. Taxonomic research on the genus is rather difficult because of the limited material available for study. Aside from the types of C. castanotis and C. occidentalis housed at the Natural History Museum in London, and the type of C. ecaudatus at the Australian Museum in Sydney, there are fewer than 30 other modern specimens in other collections scattered around the world. Examining skeletal and dental characters for several specimens, and using a combination of traditional morphology, morphometrics, palaeontology and molecular phylogenetics, we have identified two distinct species, C. ecaudatus and C. yirratji sp. nov., with C. ecaudatus having two distinct subspecies, C. e. ecaudatus and C. e. occidentalis. We use palaeontological data to reconstruct the pre-European distribution of the two species, and review the ecological information known about these extinct taxa.